2020
DOI: 10.3390/biom10121629
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]Ga-Pentixafor for PET Imaging of Vascular Expression of CXCR-4 as a Marker of Arterial Inflammation in HIV-Infected Patients: A Comparison with 18F[FDG] PET Imaging

Abstract: People living with human immunodeficiency virus (PLHIV) have excess risk of atherosclerotic cardiovascular disease (ASCVD). Arterial inflammation is the hallmark of atherogenesis and its complications. In this study we aimed to perform a head-to-head comparison of fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography ([18F]FDG PET/CT) and Gallium-68 pentixafor positron emission tomography/computed tomography [68Ga]Ga-pentixafor PET/CT for quantification of arterial inflammation in PLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Cardiovascular risk factors included in the study included smoking, hypertension, dyslipidemia, diabetes, C-reactive protein (CRP) (≥ 3 mg/L), obesity, family history of cardiovascular disease and history of cardiovascular diseases. One study [10] reported only imaging outcome metrics and 5 studies [9,[11][12][13][14] reported imaging outcome metrics and clinical correlation metrics. Lawal et al [10] reported imaging outcome indicators of atherosclerotic lesion uptake of [ 68 Ga]Ga -pentixafor and [ 18 F]-FDG; Lu et al [9] reported imaging outcome indicators of lesion uptake of [ 68 Ga]Ga -pentixafor and [ 18 F]-FDG and correlation indicators of tracer uptake with cardiovascular risk factors; Kircher et al [11] reported imaging outcome indicators of lesion uptake of [ 68 Ga]Ga -pentixafor and [ 18 F]-FDG and correlation indicators of tracer uptake with plaque calci cation; Li et al [12,13] reported imaging outcome indicators of lesion uptake of [ 68 Ga]Ga -pentixafor and correlation indicators of tracer uptake with cardiovascular risk factors; Weiberg et al [14] reported imaging outcome indicators of lesion uptake [ 68 Ga]Ga -pentixafor and also reported correlation indicators of tracer uptake with cardiovascular risk factors, correlation indicators of tracer uptake with plaque calci cation and correlation indicators of cardiovascular risk factors with plaque calci cation.…”
Section: Basic Characteristics Of Included Studies and Quality Evalua...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiovascular risk factors included in the study included smoking, hypertension, dyslipidemia, diabetes, C-reactive protein (CRP) (≥ 3 mg/L), obesity, family history of cardiovascular disease and history of cardiovascular diseases. One study [10] reported only imaging outcome metrics and 5 studies [9,[11][12][13][14] reported imaging outcome metrics and clinical correlation metrics. Lawal et al [10] reported imaging outcome indicators of atherosclerotic lesion uptake of [ 68 Ga]Ga -pentixafor and [ 18 F]-FDG; Lu et al [9] reported imaging outcome indicators of lesion uptake of [ 68 Ga]Ga -pentixafor and [ 18 F]-FDG and correlation indicators of tracer uptake with cardiovascular risk factors; Kircher et al [11] reported imaging outcome indicators of lesion uptake of [ 68 Ga]Ga -pentixafor and [ 18 F]-FDG and correlation indicators of tracer uptake with plaque calci cation; Li et al [12,13] reported imaging outcome indicators of lesion uptake of [ 68 Ga]Ga -pentixafor and correlation indicators of tracer uptake with cardiovascular risk factors; Weiberg et al [14] reported imaging outcome indicators of lesion uptake [ 68 Ga]Ga -pentixafor and also reported correlation indicators of tracer uptake with cardiovascular risk factors, correlation indicators of tracer uptake with plaque calci cation and correlation indicators of cardiovascular risk factors with plaque calci cation.…”
Section: Basic Characteristics Of Included Studies and Quality Evalua...mentioning
confidence: 99%
“…Quality evaluation was performed with the QUADAS-2 tool. Risk of bias: for case selection, 5 studies [9,10,11,13,14] were medium risk, with the main risk arising from continuity or randomization of patient inclusion; for trials to be evaluated, 1 study [13] was high risk and 5 studies [9][10][11][12]14] were medium risk, with the main risk arising from the implementation of blinding and the determination of thresholds; for gold standard 4 studies [10,[12][13][14] were medium risk, with the main risk arising from the implementation of the blinding method; for case, ow and progression, 2 studies [12,13] were high risk and 1 study [14] was a medium risk, with the main risk arising from the completeness of the case inclusion analysis and the appropriate interval. All studies had a low risk of clinical applicability.…”
Section: Basic Characteristics Of Included Studies and Quality Evalua...mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical Data First used in hematologic malignancies, 94 68 Ga-Pentixafor has been used for imaging of atherosclerosis in the carotid arteries, 93,127 aorta, 96 and coronary arteries. 97 Identification of inflammatory areas of the myocardium post-myocardial infarction have been described both ex vivo 98 and in vivo.…”
Section: Chemokine Receptor (Cxcr)-based Imagingmentioning
confidence: 99%
“…99 Data suggest that there is good correlation between 18 F-FDG-PET-positive and 68 Ga-Pentixafor-positive areas when evaluating atherosclerosis. 127 While there is currently no published report of CXCR4 used in clinical imaging of sarcoidosis, CXCR4 could become a viable tracer target as it has been implicated in granuloma formation and macrophage-mediated inflammation. 128 It has also been used for visualization of inflammation of cardiac atherosclerotic plaques 97 which have generally lower inflammatory cell counts than sarcoid granulomassuggesting 68 Ga-Pentixafor could have good sensitivity for cardiac sarcoidosis.…”
Section: Chemokine Receptor (Cxcr)-based Imagingmentioning
confidence: 99%